Effect of triple junctions on deformation twinning in a nanostructured Cu–Zn alloy: A statistical study using transmission Kikuchi diffraction - Liu, Silu; Ma, Xiaolong; Li, Lingzhen; Zhang, Liwen; Trimby, Patrick W.; Liao, Xiaozhou; Li, Yusheng; Zhao, Yonghao; Zhu, Yuntian (Beilstein Journal of Nanotechnology, 2016)
Scanning electron microscopy transmission Kikuchi diffraction is able to identify twins in nanocrystalline material, regardless of their crystallographic orientation. In this study, it was employed to characterize deformation twins in Cu/10 wt % Zn processed by high-pressure torsion. It was found that in 83% of grains containing twins, at least one twin intersects with a triple junction. This suggests that triple junctions could have promoted the nucleation of deformation twins. It should be cautioned that this technique might be unable to detect extremely small nanoscale twins thinner than its step size.
Keywords: nanocrystalline materials; transmission Kikuchi diffraction; triple junctions; twins